Monetary Transmission Mechanism and Behavior of Bank Negara Malaysia - Ramlee, Mohd Helmi (2010)
In order to achieve an effective monetary policy, recognising the main transmission mechanism channels that contributes in propagating monetary innovations to the real economic activity is essential. It is also important to ensure that there is a full passthrough from policy rate to the retail rates. This study attempts to identify the relative importance of monetary transmission mechanism channels in Malaysia. A VAR (Vector Autoregression) method is employed to study the propagation of monetary disturbances to the economy. In order to assess the relative importance of transmission channels, each channel will be exogenised and the response of output with respect to monetary shock is extracted and compared among channels. The empirical results show that the credit channel appears to be the most important channel, followed by exchange rate channel, interest rate channel and asset price channel. It is also imperative to understand the central bank behavior in its policy conduct. By using Taylor rule, Malaysia does conform to the Taylor’s principle over the long term period. Other countries that were included in this study namely United States, United Kingdom, Indonesia and Thailand also conform to the Taylor’s principle aside from the Philippines. This finding suggests that the Central Bank of Malaysia has performed the appropriate policy response in the past, in order to achieve its goal in sustainable growth and price stability.